Binary Logistic Regression Analysis of Quarter-Life Crisis Symptoms on Sleep Difficulties in Early Indonesian Adulthood (Jurnal Matematika, Statistika dan Komputasi, 2025)
Quarter-life crisis and sleep difficulties are psychological phenomena commonly experienced during early adulthood. A 2017 LinkedIn survey revealed that 75% of respondents had experienced a quarter-life crisis. The WHO in 2020 reported that 19.1% of the global population suffered from sleep difficulties. In Indonesia, a similar trend has been observed. This study aims to identify quarter-life crisis symptoms that influence sleep difficulties among individuals in early adulthood, using a binary logistic regression model. Binary logistic regression is used when the response variable is dichotomous, estimating the probability of an outcome based on several predictor variables. This quantitative research uses secondary data from the fifth wave of the Indonesian Family Life Survey (IFLS 5). The response variable is sleep difficulty (yes/no), while the predictor variables include aspects of psychological health and coping efforts, such as difficulty concentrating, feeling disturbed, feeling pressured, requiring effort, inability to start something, hope for the future, future expectations, feeling of fear, feeling isolated, life satisfaction, happiness, religious obedience, and smoking behavior. The results showed that among females, significant predictors included difficulty concentrating, feeling disturbed, fear, isolation, and happiness. Among males, significant predictors included difficulty concentrating, feeling disturbed, requiring effort, inability to start something, fear, and smoking behavior. These results indicate that certain psychological symptoms related to quarter-life crisis significantly affect sleep difficulties, with different patterns between genders. It can be concluded that gender-specific psychological interventions may help reduce sleep-related issues among early adults experiencing a quarter-life crisis.
Keywords: Binary logistic regression model; Quarter-life crisis; Sleep difficulties; Early adulthood